The Concept of Substitute Heirs: A Comparative Analysis between the Compilation of Islamic Law (KHI) and Customary Law amongst Muslim Communities in Pemalang Regency - Imaro Sidqi; Yasni Efyanti; Rahmad Setyawan; Muh Zaitun Ardi; Doli Witro; Muslih Muslih (UIN Sunan Kalijaga Yogyakarta, 2026)
This study was prompted by conceptual differences regarding substitute heirs between the Compilation of Islamic Law (KHI) and customary law practised by Muslim communities in Pemalang Regency. These differences reflect the dynamics of the application of Islamic inheritance law at the local level, which does not always align with formal legal norms. This study aims to examine the dynamics of the concept of substitute heirs and to analyse them comparatively between the provisions in the KHI and the practices of customary law within the local community. This is a field study employing a socio-legal approach and utilising comparative law theory. Data were collected through observation, interviews with eleven key informants, and a literature review, which were subsequently analysed qualitatively. The findings indicate that the KHI normatively restricts the substitution of heirs to specific conditions as stipulated in Article 185. Conversely, customary law practices amongst the Muslim community in Pemalang Regency permit a grandchild to replace the primary heir (a child) even whilst that heir is still alive; an adopted child may replace their adoptive parent; and a grandchild acting as a substitute heir may restrict (hijab) the share of the inheritance due to the biological siblings of the heir they are replacing. These differences are influenced by deeply rooted social constructs that have developed as a legal culture within the community. The implications of this research indicate that the Compilation of Islamic Law (KHI) remains an ideal normative reference, whilst customary law functions as a ‘living law’ that is adaptive and responsive to the social needs of the community. Therefore, the relationship between the two cannot be viewed dichotomously, but rather as a dialectic between formal law and ever-evolving social practices. Penelitian ini dilatarbelakangi oleh adanya perbedaan konseptual mengenai ahli waris pengganti antara Kompilasi Hukum Islam (KHI) dan hukum adat yang berlaku pada masyarakat Muslim di Kabupaten Pemalang. Perbedaan tersebut merefleksikan dinamika penerapan hukum kewarisan Islam di tingkat lokal yang tidak selalu sejalan dengan norma hukum formal. Penelitian ini bertujuan untuk mengkaji dinamika konsep ahli waris pengganti serta menganalisisnya secara komparatif antara ketentuan dalam KHI dan praktik hukum adat pada masyarakat setempat. Penelitian ini merupakan penelitian lapangan dengan pendekatan sosio-legal serta menggunakan teori perbandingan hukum. Data dikumpulkan melalui observasi, wawancara terhadap sebelas informan kunci, dan studi literatur, yang kemudian dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa KHI secara normatif membatasi penggantian ahli waris hanya pada kondisi tertentu sebagaimana diatur dalam Pasal 185. Sebaliknya, praktik hukum adat pada masyarakat Muslim di Kabupaten Pemalang, memperbolehkan cucu menggantikan kedudukan ahli waris utama (anak) meskipun ahli waris tersebut masih hidup, anak angkat dapat menggantikan kedudukan orangtua angkatnya dan cucu sebagai ahli waris pengganti dapat membatasi (hijab) bagian harta warisan saudara kandung dari ahli waris yang digantikan. Perbedaan tersebut dipengaruhi oleh konstruksi sosial yang telah mengakar dan berkembang sebagai budaya hukum dalam masyarakat. Implikasi penelitian ini menunjukkan bahwa KHI tetap menjadi rujukan normatif yang bersifat ideal, sedangkan hukum adat berfungsi sebagai living law yang adaptif dan responsif terhadap kebutuhan sosial masyarakat. Oleh karena itu, hubungan antara keduanya tidak dapat diposisikan secara dikotomis, melainkan sebagai bentuk dialektika antara hukum formal dan praktik sosial yang terus berkembang.